(untitled) (Journal of Academic Research, 2024)
This research deals with identifying the era of Professor Omar by explaining his distinguished and blessed efforts in his writings, and the diversity, distinction, mastery, and creativity that these books contain. Its importance lies in knowing his approach and the observation, investigation, criticism and accuracy contained in his books, and the methods and guidance they contain that will benefit him greatly. The problem of this research revolves around the leadership of Professor Omar Al-Majzoub in scientific research, introducing his writings and their scientific, cognitive and research value, and the importance of these writings and this leadership.